Learning and teaching in the primary classroom - Galton, Maurice J.
Providing a framework for understanding the individual needs of pupils, this title describes how you can tailor your teaching methods to maximise learning. It explores how learning is conceptualised, direct instruction, interactive teaching teaching as scaffolding, and how to overcome obstacles to learning